If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 = g + 15 Reorder the terms: -22 = 15 + g Solving -22 = 15 + g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. -22 + -1g = 15 + g + -1g Combine like terms: g + -1g = 0 -22 + -1g = 15 + 0 -22 + -1g = 15 Add '22' to each side of the equation. -22 + 22 + -1g = 15 + 22 Combine like terms: -22 + 22 = 0 0 + -1g = 15 + 22 -1g = 15 + 22 Combine like terms: 15 + 22 = 37 -1g = 37 Divide each side by '-1'. g = -37 Simplifying g = -37
| 4/x=[72/40]2 | | h/5-h/3=7/15 | | 8(5-2v)-8=3v+13 | | -1/3x-1/2=3/5 | | -5+12=16x-2-15x | | 2(4x)=2x | | 4(3x+1)=3x-7x | | 7.7a-5.8a= | | 13y=12(y+8) | | X-(x*0.05)=800 | | 16y=40+8y | | -9(x-9)=7x+17 | | 1+44=-5(8x-9) | | -22=4(v-8)-6v | | 123-v=179 | | s^2=45-4s-s^2 | | .3/.2=18/? | | X/3- | | 6w+3w=27 | | 3x-450=2816 | | V/-3.3=-14.8 | | -5(5n-5)+3n=0 | | -3y-8x=12 | | 8sin(2pi/3) | | y=(x+2)(x-(3+i))(x+(3-i)) | | 6x+26=8x+36 | | =(x+2)(x-(3+i))(x+(3-i)) | | 9z+z=9z+5 | | -9+3y-x=0 | | 0=100-0.01(x^2) | | 18x-15/3 | | 6(x+7)-11=0 |